Employment guarantee, civil society and Indian democracy - Shah, Mihir (2007)
Even as we celebrate 60 years of Indian democracy, with millions of our people hungry, cynical and insecure, and living under the barrel of the gun (of the state of the extremists), we need to worry about the reach and quality of our political process. The National Rural Employment Guarantee Act has the potential to provide a "big push" in India's regions of distress. For NREGA to be able to realise its potential, the role of civil society organisations is critical. But this calls for a new self-critical politics of fortitude, balance and restraint. - Reproduced.
Keywords: Democracy - India; Civil society - India; Employment - India; Employment